2007
DOI: 10.1172/jci28034
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and neutrophils are the targets for immune suppression by glucocorticoids in contact allergy

Abstract: Glucocorticoids (GCs) are widely used in the treatment of allergic skin conditions despite having numerous side effects. Here we use Cre/loxP-engineered tissue-and cell-specific and function-selective GC receptor (GR) mutant mice to identify responsive cell types and molecular mechanisms underlying the antiinflammatory activity of GCs in contact hypersensitivity (CHS). CHS was repressed by GCs only at the challenge phase, i.e., during reexposure to the hapten. Inactivation of the GR gene in keratinocytes or T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
225
2
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(248 citation statements)
references
References 54 publications
13
225
2
8
Order By: Relevance
“…Murine BMDM were prepared as described recently (9). All cells were cultivated in 5% CO 2 at 37°C and subcultured every 3-4 days.…”
Section: Methodsmentioning
confidence: 99%
“…Murine BMDM were prepared as described recently (9). All cells were cultivated in 5% CO 2 at 37°C and subcultured every 3-4 days.…”
Section: Methodsmentioning
confidence: 99%
“…However, when the analysis of GR dim mice was expanded to other inflammatory processes, we observed a failure of GCs to exert a full anti-inflammatory response. This was the case for exogenous actions of GCs in contact allergy and for the modulatory role of endogenous GCs in septic shock and for the early response during wound healing exhibiting elevated cytokine and chemokine expression (Grose et al, 2002;Tuckermann et al, 2007). As a side effect GC inhibition of bone formation occur in these mice.…”
Section: Resultsmentioning
confidence: 99%
“…From the croton oil experiments one could conclude that dimerized-induced DNA binding can be omitted for suppression of inflammatory skin diseases. However, recent studies in contact hypersensitivity, a model for contact dermatitis and thus an inflammatory type of a different mechanism revealed that more than transrepression of the GR is required for suppression of inflammation (Tuckermann et al, 2007). This has consequences for therapeutic strategies, for example one would expect that function selective GR ligands (SEGRAs) that address the transrepression activity with the hope to reduce atrophy of the skin (Schoepe et al, 2006) would be potent in the treatment of irritant dermatitis, but less in contact allergy.…”
Section: Exogenous Gc Action In Skin Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exposure of DCs to nickel sulfate stimulates signal transduction pathways and augments expression of MHC class II and several costimulatory molecules in different manners compared to that of DNFB (16). Macrophages are a subpopulation of cells in the mouse dermis that have gained attention as a useful therapeutic target for contact allergies (17)(18)(19). In a previous study, we examined macrophage inflammatory protein 2 (MIP-2) expression in topically DNFB-applied skin and the DNFB-treated RAW 264.7 cells (19).…”
Section: Introductionmentioning
confidence: 99%